Gender-typed career plans – To what extent are male high school students interested in teaching? - Berweger, Simone; Kappeler, Christa; Keck Frei, Andrea; Bieri Buschor, Christine (Swiss Journal of Educational Research, 2018)
This paper investigates to what extent 16-year old Swiss male high school students are interested in a teaching professional career. It analyses factors contributing to the intention to choose teaching after graduating from academic high school. The results of a survey (n=388), conducted in the canton of Zurich, show that male adolescents report low interest in teaching at an early stage of their career orientation. Results of a sequential logistic regression analysis reveal a number of factors that are relevant to the participants’ intention to opt for teaching as a career. Interest in teaching and a good work-life balance, including hobbies such as sports, have a positive effect, while considerations regarding financial security and opportunities to work part-time, in contrast, have a negative impact on opting for choosing the field of teaching.